Tropical Plant Biology - Ming, Ray.; Arruda, Paulo; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
Tropical Plant Biology covers the most rapidly advancing aspects of tropical plant biology including physiology, evolution, development, cellular and molecular biology, genetics, genomics, genomic ecology, and molecular breeding. It publishes articles of original research, but it also accepts review articles and publishes occasional special issues focused on a single tropical crop species or breakthrough. Information published in this journal guides effort to increase the productivity and quality of tropical plants and preserve the world$1 (Bs plant diversity. The journal serves as the primary source of newly published information for researchers and professionals in all of the aforementioned areas of tropical science.s
Keywords: Plant ecology; Plant science; Botany; Plant breeding; Transgenic organisms; Plant Sciences; Plant Genetics and Genomics; Plant Breeding/Biotechnology.; Plant Ecology; Transgenics